Transforming Girls : The Work of Nineteenth-Century Adolescence - Pfeiffer, Julie (Julie Kristine) (Book collections on Project MUSE., 2021)
"Transforming Girls: The Work of Nineteenth-Century Adolescence explores the paradox of the nineteenth-century girls' book. On the one hand, early novels for adolescent girls rely on gender binaries and suggest that girls must accommodate and support a patriarchal framework to be happy. On the other, they provide access to imagined worlds in which teens are at the center. The early girls' book frames female adolescence as an opportunity for productive investment in the self. This is a space where mentors who trust themselves, the education they provide, and the girl's essentially good nature neutralize the girl's own anxieties about maturity. Drawing on best-selling novels in the United States and Germany (where this genre is referred to as Backfischliteratur), Transforming Girls reframes our understanding of the history of the girls' book and provides insightful readings of forgotten bestsellers. It also outlines an alternate model for imagining adolescence and supporting adolescent girls. The awkward adolescent girl-so popular in mid-nineteenth-century fiction for girls-remains a valuable resource for understanding contemporary girls and stories about them"--